Dietary and physical activity adaptations to alternate day modified fasting: implications for optimal weight loss - Klempel, Monica C (BioMed Central, 2010)
BACKGROUND: Alternate day modified fasting (ADMF) is an effective strategy for weight loss in obese adults. OBJECTIVE: The objective of this study was to examine the dietary and physical activity adaptations that occur during short-term ADMF, and to determine how these modulations affect rate of weight loss. METHODS: Sixteen obese subjects (12 women/4 men) completed a 10-week trial consisting of 3 phases: 1) 2-week control phase, 2) 4-week ADMF controlled feeding phase, and 3) 4-week ADMF self-selected feeding phase. RESULTS: Body weight decreased (P < 0.001) by 5.6 ± 1.0 kg post-treatment. Energy intake on the fast day was 26 ± 3% of baseline needs (501 ± 28 kcal/d). No hyperphagic response occurred on the feed day (95 ± 6% of baseline needs consumed, 1801 ± 226 kcal/d). Daily energy restriction (37 ± 7%) was correlated to rate of weight loss (r = 0.42, P = 0.01). Dietary fat intake decreased (36% to 33% of kcal, P < 0.05) with dietary counseling, and was related to rate of weight loss (r = 0.38, P = 0.03). Hunger on the fast day decreased (P < 0.05) by week 2, and remained low. Habitual physical activity was maintained throughout the study (fast day: 6416 ± 851 steps/d; feed day: 6569 ± 910 steps/d). CONCLUSION: These findings indicate that obese subjects quickly adapt to ADMF, and that changes in energy/macronutrient intake, hunger, and maintenance of physical activity play a role in influencing rate of weight loss by ADMF.